2011
DOI: 10.1016/j.cpc.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

3D Magneto-hydrodynamic simulations of Parker instability with cosmic rays

Abstract: This study investigates Parker instability in an interstellar medium (ISM) near the Galactic plane using threedimensional magneto-hydrodynamic simulations. Parker instability arises from the presence of a magnetic field in a plasma, wherein the magnetic buoyant pressure expels the gas and cause the gas to move along the field lines. The process is thought to induce the formation of giant molecular clouds in the Galaxy. In this study, the effects of cosmicray (CR) diffusion are examined. The ISM at equilibrium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Cosmic rays can play a dynamical role in the structure and evolution of the interstellar as well as intergalactic medium. For instances, from the hydrodynamic perspective, cosmic rays can affect instabilities, such as, Parker instability, Jeans instability, magnetorotional instability (e.g., Parker 1969Parker , 1966Hanasz & Lesch 2000Ryu et al 2003;Kuwabara et al 2004;Kuwabara & Ko 2006;Ko & Lo 2009;Lo et al 2011;Kuwabara & Ko 2015;Heintz & Zweibel 2018;Heintz et al 2020;Kuwabara & Ko. 2020), and they can modify structures and outflows (e.g., Ko et al 1991;Yang et al 2012;Girichidis et al 2016;Dorfi & Breitschwerdt 2012;Recchia et al 2016;Ruszkowski et al 2017;Mao & Ostriker 2018;Farber et al 2018;Holguin et al 2019;Dorfi et al 2019;Yu et al 2020;Recchia 2020;Ramzan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cosmic rays can play a dynamical role in the structure and evolution of the interstellar as well as intergalactic medium. For instances, from the hydrodynamic perspective, cosmic rays can affect instabilities, such as, Parker instability, Jeans instability, magnetorotional instability (e.g., Parker 1969Parker , 1966Hanasz & Lesch 2000Ryu et al 2003;Kuwabara et al 2004;Kuwabara & Ko 2006;Ko & Lo 2009;Lo et al 2011;Kuwabara & Ko 2015;Heintz & Zweibel 2018;Heintz et al 2020;Kuwabara & Ko. 2020), and they can modify structures and outflows (e.g., Ko et al 1991;Yang et al 2012;Girichidis et al 2016;Dorfi & Breitschwerdt 2012;Recchia et al 2016;Ruszkowski et al 2017;Mao & Ostriker 2018;Farber et al 2018;Holguin et al 2019;Dorfi et al 2019;Yu et al 2020;Recchia 2020;Ramzan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of CRs on various instabilities has been studied by means of linear analysis and MHD simulations, for instance, the evolution of Parker instability (Parker 1966;Hanasz 1997;Hanasz & Lesch 2000;Ryu et al 2003;Kuwabara et al 2004;Lo et al 2011), Parker-Jeans instability (Kuznetsov & Ptuskin 1983;Kuwabara & Ko 2006), magneto-rotational instability (Khajenabi 2012), Kelvin-Helmholtz instability (Suzuki et al 2014), and also galactic dynamo (Parker 1992;Hanasz et al 2004Hanasz et al , 2009. The results of these works showed that in some cases the growth rate has some intriguing dependence on the cosmic ray pressure and the coupling of CR and thermal plasma (i.e., the cosmic ray diffusion coefficient).…”
Section: Introductionmentioning
confidence: 99%
“…For instances, in the past couple decades, efforts have been made on the understanding of the influencing of cosmic rays on instabilities related to interstellar medium (such as, Parker instability, Jeans instability, magnetorotional instability, see, e.g. Parker 1966; Corresponding author: C. M. Ko cmko@astro.ncu.edu.tw Kuznetsov & Ptuskin 1983;Hanasz & Lesch 2000Ryu et al 2003;Kuwabara et al 2004;Kuwabara & Ko 2006;Ko & Lo 2009;Lo et al 2011;Kuwabara & Ko 2015;Heintz & Zweibel 2018;Heintz et al 2020); and on cosmic ray modified structures and outflows (e.g., shocks, galactic halo, stellar and galactic winds, see e.g., Drury & Völk 1981;McKenzie & Völk 1982;Ko et al 1997;Ko 2001;Ghosh & Ptuskin 1983;Ko et al 1991;Ko 1991a;Ko et al 1988;Ko 1991b;Ipavich 1975;Zirakashvili et al 1996;Everett et al 2008;Yang et al 2012;Girichidis et al 2016;Recchia et al 2016;Ruszkowski et al 2017;Mao & Ostriker 2018;Farber et al 2018;Holguin et al 2019;Dorfi & Breitschwerdt 2012;Dorfi et al 2019;Yu et al 2020). Especially, in the past ten years or so, there are a lot of attentions on cosmic ray modified galactic wind.…”
mentioning
confidence: 99%